Plantation workers resistance and accommodation (Univ. of Hawaii Press, 1993)
The lives of plantation laborers are usually depicted in terms reminiscent of eighteenth-century soldiering - nasty, brutish, and short. While the structures governing their lives varied from place to place and over time, the authoritarian and coercive nature of the plantation system itself remained pervasive. Recent research has shown, however, that the responses of plantation workers to the demands of their workplace were in fact quite variable, from acquiescence to outright rebellion, from collaboration with management to attempts to carve out private lives offering a sense of self-esteem. By focusing on the relationship between resistance and accommodation, Plantation Workers provides the first systematic examination of the kinds of responses offered to the plantation regime. The essays cast an analytical eye over the contexts of workers' lives within which resistance and accommodation were played out. Looking at these responses as two aspects of the same activity, contributors account for the circumstances under which worker resistance could be mounted and, conversely, employer pressure sustained. Most chapters focus on the Pacific Islands, but the collection includes studies from Latin America and Australia, enabling a comparative evaluation of the actual working experiences of plantation laborers and a more nuanced understanding of the people who labored in the "factories in the field." Plantation Workers is a valuable addition to Pacific Islands historiography, comparative labor history, the history of race relations, and peasant studies.